Sistem Informasi Akuntansi Penjualan Spare Part pada PT. Hadji Kalla Cabang Urip Sumoharjo Makassar - Siswati Rachman; Kurniaty Kurniaty; Kapriani Kapriani (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This research was conducted at PT Hadji Kalla Branch Information Sumiharjo Makassar with the aim to determine the accounting information system sales of spare parts PT Hadji Kalla Branch Information Sumiharjo Makassar. This type of research is descriptive qualitative, the authors describe the results of observations and interviews and analyzing the data obtained in the field. After analysis and discussion, the authors obtained the conclusion that the information system of accounting of sales of spare parts has been applied in accordance with the theory so as to produce information that is reliable enough, such as the existence of conformity between the task and the responsibility of each part, functioning optimally each function is related, the availability of the documents required, the conformity of the accounting records used, as well as the suitability of procedures that make up the system.